2017
DOI: 10.1111/ctr.13053
|View full text |Cite|
|
Sign up to set email alerts
|

Feelings of indebtedness and guilt toward donor and immunosuppressive medication adherence among heart transplant (HTx) patients, as assessed in a cross‐sectional study with the Basel Assessment of Adherence to Immunosuppressive Medications Scale (BAASIS)

Abstract: Physicians and nurses should inquire about the presence of guilt feelings, as they might be associated with NA to medications after HTx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 26 publications
5
27
1
Order By: Relevance
“…In the last decade, older HT candidates became eligible for transplantation as a result of eliminating age restrictions. In a recent study, we showed that older patients in our cohort displayed better adherence to immunosuppressive medications than younger patients, these findings are consistent with previously published studies in which older patients had better medication adherence; (ii) possible reduction in ischemia reperfusion injury in more recent years due to better operative techniques and surgical skills; (iii) improved immunohistochemical and immunopathological experience and techniques, as well revised classification for rejection may have led to more accurate detection of major rejections in more recent years. These could have contributed to reduction in interobserver variability, as well to minimizing a “false‐positive” reading; (iv) Frailty has recently been recognized as an important predictor for adverse outcomes in HT and is associated with increased mortality and increased risk for graft dysfunction .…”
Section: Discussionsupporting
confidence: 90%
“…In the last decade, older HT candidates became eligible for transplantation as a result of eliminating age restrictions. In a recent study, we showed that older patients in our cohort displayed better adherence to immunosuppressive medications than younger patients, these findings are consistent with previously published studies in which older patients had better medication adherence; (ii) possible reduction in ischemia reperfusion injury in more recent years due to better operative techniques and surgical skills; (iii) improved immunohistochemical and immunopathological experience and techniques, as well revised classification for rejection may have led to more accurate detection of major rejections in more recent years. These could have contributed to reduction in interobserver variability, as well to minimizing a “false‐positive” reading; (iv) Frailty has recently been recognized as an important predictor for adverse outcomes in HT and is associated with increased mortality and increased risk for graft dysfunction .…”
Section: Discussionsupporting
confidence: 90%
“…A corresponding overall non‐adherence rate of 19% could be assessed by HCW judgment. These rates appear comparable to overall non‐adherence rates ranging between 13% and 50% reported by others …”
Section: Discussionmentioning
confidence: 98%
“…Patients found it difficult to accept their new kidney because of a number of different situations including: the side effects of medication, fear of transplant rejection and feeling obliged to make the most of life because of the ‘gift’ of a transplant 24–27. It has been reported that concern about the potential lifespan of the transplanted kidney may be the biggest stressor immediately after transplant, this fear subsides with time 8.…”
Section: Discussionmentioning
confidence: 99%